Prognostic Power of Pulmonary Arterial Compliance Is Boosted by a Hemodynamic Unloading Test With Glyceryl Trinitrate in Heart Failure Patients With Post-capillary Pulmonary Hypertension - Rieth, Andreas J.; Grün, Dimitri; Zarogiannis, Georgios; Kriechbaum, Steffen D.; Wolter, Sebastian; Richter, Manuel J.; Tello, Khodr; Krüger, Ulrich; Mitrovic, Veselin; Rosenkranz, Stephan; Hamm, Christian W.; Keller, Till (Frontiers in Cardiovascular Medicine, 2022)
Background Pulmonary hypertension (PH) is an established risk factor in patients with heart failure (HF). However, right heart catheterisation (RHC) and vasoreactivity testing (VRT) are not routinely recommended in these patients. Methods The primary objective of the present study was to explore the impact of VRT using sublingual glyceryl trinitrate (GTN) on transplant/ventricular assist device-free survival in HF patients with post-capillary PH. RHC parameters were correlated retrospectively with the primary outcome. Results The cohort comprised 154 HF patients with post-capillary PH undergoing RHC with GTN-VRT at a tertiary heart failure centre. Multiple parameters were associated with survival. After adjustment for established prognosis-relevant clinical variables from the MAGGIC Score, variables with the most relevant odds ratios (OR) obtained after GTN-VRT were: calculated effective pulmonary arterial (PA) elastance (adjusted OR 2.26, 95%CI 1.30–3.92; p = 0.004), PA compliance (PAC-GTN; adjusted OR 0.45, 95%CI 0.25–0.80; p = 0.006), and total pulmonary resistance (adjusted OR 2.29, 95%CI 1.34–3.93; p = 0.003). Forest plot analysis including these three variables as well as PAC at baseline, delta PAC, and the presence of combined post- and pre-capillary PH revealed prognostic superiority of PAC-GTN, which was confirmed by Kaplan-Meier analysis. Conclusions In our cohort of symptomatic HF patients with post-capillary PH, improved PAC after administration of GTN was associated with survival independent of established hemodynamic and clinical risk factors. VRT using GTN may be better described as unloading test due to GTN's complex effects on the circulation. This could be used for advanced prognostication and should be investigated in further studies.